PKM PENINGKATAN PEMAHAMAN PERAN KOPERASI DI KALANGAN PELAJAR SMK GAJAH MADA BANDAR LAMPUNG - Mamay Komarudin; Munawaroh Munawaroh; Wahyu Widodo (Gapenas Publisher, 2023)
This study aims to explore students' understanding and participation of cooperatives at SMK Gajahmada Bandar Lampung, focusing on student perceptions, socialization of cooperatives by schools, and students' interest in participation in cooperatives. The methods used included in-depth interviews with three student informants and observation of school cooperative activities, to identify their level of understanding and participation in school cooperatives. The results showed that students' understanding of cooperatives is very limited, the majority only consider cooperatives as a place for purchasing school needs without understanding the basic principles and benefits of cooperatives as economic entities oriented to the interests of their members. This study also revealed that cooperative socialization by schools has not been effective, resulting in low interest of students to participate in cooperative activities. This research suggests the need to increase cooperative socialization and education efforts in schools, including the integration of cooperative education into the curriculum and the development of supportive extracurricular activities, to increase student understanding and participation in cooperatives. By strengthening cooperative education and socialization, students can gain a better understanding of the cooperative concept, increase their interest in getting involved, and tap into the potential of cooperatives as a means for economic learning and entrepreneurial skills development